Iconography of the Holy King Ladislaus in Zagreb Diocese in Late 17th and Early 18th Century. New Reading of the Past in Central European Context - Botica, Dubravka (Array, 2012)
The paper discusses the development of the iconographical models of the image of King Ladislaus in the Middle Ages, as the Holy King and a brave warrior and knight, based on the legend of his life. Representations of King Ladislaus were wide-spread in the Hungarian lands, thus also in the Zagreb Diocese founded by Ladislaus in 1094. In the second half of the 17th and in early 18th century there was a renewed interest for the cult of King Ladislaus, represented in several important commissions of the Zagreb Chapter. Under the influence of contemporary historiography, especially the writings of J. Rattkay of Veliki Tabor and P. R. Vitezović, Ladislaus was interpreted as a local ruler and venerated as the protector of the Triune Kingdom of Croatia, Slavonia and Dalmatia. After the altars in the Zagreb Diocese (Cathedral, Vrapče, Sisak), the thematically elaborate painted cycle from Zagreb Cathedral and the fresco paintings in the Illyrian-Hungarian College in Bologna which accentuate the new role of King Ladislaus, the “end” of the subject was marked by Bishop Branjug’s commission of the construction and decoration of the parish church of St Ladislaus in Pokupsko (1736-39). The theatrically conceived main altar includes an iconographical programme envisaged within the Zagreb cultural and political circle. Similarities in the interpretation of a holy king can be discerned in Bohemian art in the changes of the iconography of St Wenceslaus, which reflect the wide-spread idea of the return to roots and the cult of local saints in Central European art of the 17th and 18th century.